RETRACTED: Heritage tourism as a direction to support sustainable tourism development in the regions and the local area - Zolotovskiy Vladimir (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001